2021
DOI: 10.3390/biom11070974
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of S100A10 Gene Expression

Abstract: S100A10, a member of the S100 family of Ca2+-binding proteins, is a widely distributed protein involved in many cellular and extracellular processes. The best recognized role of S100A10 is the regulation, via interaction with annexin A2, of plasminogen conversion to plasmin. Plasmin, together with other proteases, induces degradation of the extracellular matrix (ECM), which is an important step in tumor progression. Additionally, S100A10 interacts with 5-hydroxytryptamine 1B (5-HT1B) receptor, which influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, methylation of the GRHL2 gene promoter region in acute leukemia patients and leukemia cell lines remains unclear. As a new tumor suppressor gene, abnormal methylation of the GRHL2 gene promoter region may be a potential tumor molecular marker [15][16][17]. Therefore, this study explored the feasibility of abnormal methylation of the GRHL2 gene promoter region in patients with acute leukemia and cell lines as hematologic markers and further studied the demethylation of the GRHL2 gene by arsenide trioxide and 5-azacitidine.…”
Section: Introductionmentioning
confidence: 99%
“…However, methylation of the GRHL2 gene promoter region in acute leukemia patients and leukemia cell lines remains unclear. As a new tumor suppressor gene, abnormal methylation of the GRHL2 gene promoter region may be a potential tumor molecular marker [15][16][17]. Therefore, this study explored the feasibility of abnormal methylation of the GRHL2 gene promoter region in patients with acute leukemia and cell lines as hematologic markers and further studied the demethylation of the GRHL2 gene by arsenide trioxide and 5-azacitidine.…”
Section: Introductionmentioning
confidence: 99%
“…Several transcription factors such as activator protein-1 (AP-1) complex formed by c-Fos and c-Jun, and GRHL2, a grainyhead-like transcription factor family member, have been reported as upstream regulators of S100a10 74,75 . In this study, we identified the transient activation of IL4-STAT6 pathway regulates the expression of S100a10 in the DRN serotonin neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Contribution 3 (Głowacka et al, 2021) offers an overview of the stimuli inducing S100A10 expression and reveals that the GRHL2 transcription factor is involved in S100A10 gene transcription by binding within its intronic region.…”
Section: An Overview Of Published Articlesmentioning
confidence: 99%